Determination of Diosmin by Visible Spectrophotometry - Uma Devi, P.; Satyanarayana, K.V.V.V.; Sastry, C.S.P. (Asian Journal of Chemistry, 2010)
Three simple and sensitive spectrophotometric methods (A-C) for the determination of diosmin are described. They are based on the oxidative coupling reaction between diosmin and 4- aminophenazone (4-AP)-potassium ferricyanide [K3Fe(CN)6] (λmax 500 nm, method A); or p- N,N-dimethylphenylene diamine (DMPD)-chloramines T (CAT) (λmax 680 nm, method B); or 2,6-dichloroquinone-N-chlorimide (DCQC) (λmax 540 nm, method C). The results obtained by each proposed method is compared statistically by means of student t-test and by the F-test with that of the reported method. They are found to be in good agreement. No interferences are observed from common pharmaceutical excipients. The proposed methods are selective, simple and economical for the quantitative deter-mination of diosmin.